Marketing myopia: An interesting fact to marketers / Sharifah Zannierah Syed Marzuki and Wan Kalthom Yahya - Syed Marzuki, Sharifah Zannierah; Yahya, Wan Kalthom (Universiti Teknologi MARA Cawangan Pahang, 2005)
It is commonly believed that marketing knowledge is useful. Marketing knowledge comes in many forms and perspectives. Sellers need buyers and vice versa. In marketing, a transaction will only be completed when there is an exchange from both parties. But selling, again, is not marketing. Selling concerns itself with the tricks and techniques of getting people to exchange their cash for the product. It is not concerned with the values that the exchange is all about. It does not as marketing invariably does, view the entire business process as consisting of a tightly integrated effort to discover, create, arouse and satisfy customer needs. The customer is somebody "out there" who, with proper cunning, can be separated from his loose change. Marketers must not ignore the marketing myopia that may exist between them and their customers.